Equivalent thermal model of a permanent magnet synchronous machine - Zhao, Dawei. (2013)
Permanent magnet (PM) motors are popular choices for hybrid electric vehicle (HEV) powertrain applications. Compared to other singly fed electric machines, permanent magnet motors are smaller, lighter, more efficient and reliable.